Analysis of Traveling Strategies for Driving Omni-Wheeled Vehicle Around a Corner - Siying Long (IEEE Access, 2020)
Vehicles equipped with omnidirectional wheels can move in any direction, which means that many driving strategies are available, even for a simple task like turning a corner. However, the characteristics of each driving strategy have not yet been explored to detect what kind of strategy is suitable for what path conditions for what reasons. This study aims to clarify and compare the phenomena that occur in the possible least-time driving strategies for an omni-wheeled vehicle while it turns a corner. Three traveling strategies are proposed according to the order of rotation and turning motion, for which the possible least-time patterns are presented. Simulations are conducted to analyze the advantages of each pattern and compare the three traveling strategies for various path and corner configurations. The results show that the strategy in which the vehicle rotates during or after turning motion costs the least time. When both the path width and corner angle are small, the vehicle should turn with a large radius to maintain a high velocity. In contrast, the vehicle should turn with a small radius when the corner angle is large, even if this requires deceleration.